Food waste management innovations in the foodservice industry. (September 2018) - Martin-Rios, Carlos; Demen-Meier, Christine; Gössling, Stefan; Cornuz, Clémence
Highlights: Application of innovation theory to study food waste in the foodservice sector. Foodservice professionals implement incremental and radical food waste innovations. Introduction of different innovations is based on financial cost/benefit analysis. Professionals approach innovations from an experience-based learning perspective. Professionals lack systematic implementation of waste reduction strategies. Abstract: There is growing evidence that a significant share of global food is thrown away, with concomitant detrimental repercussions for sustainability. Reducing food waste is a key sustainability challenge for the food service industry. Despite the significance of this issue to the global foodservice industry, the link between innovation practices and food waste management has received limited attention in the academic literature. This paper uses innovation management and social constructionism to investigate interrelationships of food service provisions and innovations in waste management. It is based on the evaluation of food waste solutions and innovations that combine strategic dimensions of waste management with practice-driven initiatives, including incremental (processes and technologies) and radical innovations. The paper presents a range of waste management initiatives, showing that their implementation in the foodservice sector varies depending on management's beliefs, knowledge, goals and actions. The concepts discussed here could help practitioners to become more aware of the factors that drive the adoption of food waste innovations.